Factors influencing commercial bank financing of women owned enterprises in Nairobi county (Kenya) - Chebichi, Clare (Graduate School of Business (GSB), 2025)
Compared to large corporates, small and medium enterprises (SMEs) are usually more disadvantaged and have less access to outside capital. Given their importance and contribution to the economy, lack of access to finance is likely to hurt women-owned enterprises more than their male counterparts, thus hindering their competitiveness which could result in increased failure rates. While studies in developing economies have linked low access to bank finance among women-owned enterprises to supply factors such as failure in financial markets due to asymmetric information and agency problems, poor financial management skills, lack of collateral and high interest rates among others, the situation is not necessarily similar contextually with a developing economy like Kenya, hence the need for this study. This research examined factors that influence bank financing of Women-owned Enterprises by Commercial Banks in Nairobi County, Kenya. Specifically, it examined the effect of collateral requirements, business performance, credit worthiness and financial management skills on commercial bank financing of Women-owned Enterprises in Nairobi County, Kenya using a sample size of 388 SME owners or their managers, who were sampled through stratified random sampling techniques. From the regression analysis, the study identified financial performance as key to accessing commercial bank financing for women-owned SMEs. Additionally, it was found that accounting and budgeting business management skills were very important in increasing the chances of accessing commercial bank financing by women-owned SMEs. These findings led to the recommendation that women SME owners need to invest in acquisition of collateral assets so as to bolster their chances of securing commercial bank financing. They should consider putting in strategic efforts to enhance their performance, especially in the areas of cash flow and profits. They should also invest in building their business management skills. The study recommends that commercial banks expand the types of collateral they accept, such as savings in the bank. Furthermore, the study finds that better financial performance is crucial to accessing bank financing and advises women-owned SMEs to focus on improving their cash flow and profits. Minimizing loans from multiple lenders is also recommended to reduce the risk of default. Additionally, the study highlights the importance of accounting and budgeting skills for accessing bank financing and recommends that women business owners invest in training in these areas. The study also recommends that formal lenders engage and train women SME owners in these skills to enhance their ability to effectively utilize the funds provided to them.